Democratizing information. An analysis of the motivations that drive academics to publish - Alfaro Martínez, Raquel (2024)
Motivations are the framework that drives people’s actions, and according to several research studies, they are the basis for the success of many of the tasks that influence the moment of acting and choosing what one wishes to achieve. This paper investigates the motivations of active academics at the National University (Costa Rica) to publish their research findings financed with public funds. Based on, a mixed methodological approach, and a descriptive and exploratory research, and uses questionnaires, interviews, and content analysis as data collection techniques. At the end of the research, it was concluded that the motivations of academics are both positive and negative, it was determined that there are academically attractive criteria for these researchers, but at the same time, there are criteria that may be linked to inherently discouraging conceptions. Investigating motivations from the perspective of librarianship makes it possible to identify how these trends can influence the democratization of information. In addition to understanding how researchers are motivated by enjoyment and intellectual curiosity depending on the journal in which they publish, this helps to distinguish between intrinsic motivations, fundamental to the commitment and quality of the work, and extrinsic motivations, such as rewards or external recognition.